OSTEOPOROTIC VERTEBRAL FRACTURES: FROM DIAGNOSIS TO REHABILITATION - Spasojevic, Tijana (Acta medicae Medianae, 2024)
Osteoporotic vertebral fractures represent a significant sociomedical problem that impairs the quality of life of the elderly population. Clinical examination, supplementary diagnostic methods (X-ray, Computed Tomography – CT, Dual-Energy X-ray Absorptiometry – DXA, Lateral Vertebral Assessment – LVA) and fracture risk assessment tool (FRAX) are crucial for effective assessment of fracture severity, timely decision on treatment method, and initiation of rehabilitation. Of great practical importance is the effect of antiresorptive therapy on callus formation. In patients who suffer from osteoporosis, and despite treatment have a fracture, it is recommended not to interrupt bisphosphonate therapy, which was started several months before the diagnosed fracture. Bisphosphonates should be introduced into the treatment in a period of 2−4 months from the occurrence of the fracture, depending on the location of the fracture, that is, the time required for callus formation. Recombinant parathyroid hormone is an effective anabolic therapy that accelerates bone regeneration during fractures, increases callus volume and faster bone strength. Osteoporosis therapy should not be started without checking the total and ionized Ca, P, 25(OH)D, and PTH as well as general biochemical analyses, and then introducing antiresorptive or anabolic therapy. Rehabilitation treatment is individually designed and includes balance exercises, strength exercises, range of motion and postural training leading to improvement of spinal mobility, muscle strength and overall functionality. The aim of this review was to highlight the timely diagnosis, evaluation, and treatment of osteoporotic vertebral fractures.
Keywords: osteoporotic vertebral fractures, dual-energy x-ray absorptiometry, fracture risk assessment tool, therapy, rehabilitation